Acute Bronchiolitis in Children - Kudratova Gulsara Najmitdinovna; Kholmuradova Zilola Ergashevna (Genius Journals, 2022)
Statya posvyashchena probleme ostrogo bronchiolita u detey. Actuality of this problem does not cause doubt: according to modest estimates, more than 150 million people are registered in the world. sluchaev bronchiolitis, 7-13% of which require inpatient treatment, and 1-13% - hospitalization and separation of intensive therapy [2,12]. The most common etiological factors are viral-respiratory-synthsitial (in most cases - 90%), the main agent is rhinovirus, as well as viral influenza A and V, parainfluenza, adenovirus, coronovirus, metapneumovirus. The development of bronchiolitis in children is the first two years of life, and a number of factors are associated with it. Especially, bronchiolitis occurs in premature infants, children with bronchopulmonary dysplasia and artificial feeding, as well as development and immunodeficiency in patients with congenital diseases. Provoditsya passive immunization of children with high risk of bronchiolitis in RSV season with injectable monoclonal antibodies to RSV- Palivizumab. Purpose of the work: In this review article, the clinical manifestations and mechanisms of origin, comparative diagnosis, optimal treatment and outcome of bronchiolitis are considered.
Keywords: Bronchiolitis; premature children; clinic; treatment